2017
DOI: 10.1038/onc.2017.177
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic K-Ras upregulates ITGA6 expression via FOSL1 to induce anoikis resistance and synergizes with αV-Class integrins to promote EMT

Abstract: In many cancer types, integrin-mediated signaling regulates proliferation, survival and invasion of tumorigenic cells. However, it is still unclear how integrins crosstalk with oncogenes to regulate tumorigenesis and metastasis. Here we show that oncogenic K-RasV12 upregulates α6-integrin expression in Madin–Darby canine kidney (MDCK) cells via activation of the mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK)/Fos-related antigen 1-signaling cascade. Activated α6-integrins promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 73 publications
(88 reference statements)
0
48
0
Order By: Relevance
“…To generate double ␣6/␤4-KO and ␤1/␤4-KO cells, clonal ␤4KO cells were transduced with ␣6-targeting lentiCRISPR vector as described above, expanded and negatively selected by fluorescence activated cell sorting (FACS) based on live staining with anti-␣6 (GoH3) or anti-␤1 (AIIB2) antibodies. Antibody staining for FACS was performed as previously described (28). Alexa Fluor 488-negative cell population was collected with the BD FACSAria™ flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…To generate double ␣6/␤4-KO and ␤1/␤4-KO cells, clonal ␤4KO cells were transduced with ␣6-targeting lentiCRISPR vector as described above, expanded and negatively selected by fluorescence activated cell sorting (FACS) based on live staining with anti-␣6 (GoH3) or anti-␤1 (AIIB2) antibodies. Antibody staining for FACS was performed as previously described (28). Alexa Fluor 488-negative cell population was collected with the BD FACSAria™ flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Integrin has been shown to affect tumorigenesis via the Ras/Erk pathway [19]. However, whether ITGA1 affects tumorigenesis of CRC via the Ras/Erk pathway requires further to investigate.…”
Section: Itga1 Activates the Ras/erk Signaling Pathwaymentioning
confidence: 99%
“…K‐RAS protooncogene is one of the genes with high mutation frequency of >90% in PC, which is closely related to the development of PC and confers a unfavourable prognosis in PC patients . The somatic mutation in K‐RAS was confirmed to promote the malignant transformation of tumour cells and resistance to anticancer agents . Studies have reported that the PC cells lines carrying mutated K‐RAS showed high resistance to gemcitabine .…”
Section: Introductionmentioning
confidence: 99%
“…[7] The somatic mutation in K-RAS was confirmed to promote the malignant transformation of tumour cells and resistance to anticancer agents. [8] Studies have reported that the PC cells lines carrying mutated K-RAS showed high resistance to gemcitabine. [9] Recent evidence also suggested that mutations of K-RAS predicted an insensitivity of PC cells to erlotinib.…”
Section: Introductionmentioning
confidence: 99%